2013
DOI: 10.1063/1.4812454
|View full text |Cite
|
Sign up to set email alerts
|

The transition mechanism from a symmetric single period discharge to a period-doubling discharge in atmospheric helium dielectric-barrier discharge

Abstract: Period-doubling and chaos phenomenon have been frequently observed in atmospheric-pressure dielectric-barrier discharges. However, how a normal single period discharge bifurcates into period-doubling state is still unclear. In this paper, by changing the driving frequency, we study numerically the transition mechanisms from a normal single period discharge to a period-doubling state using a one-dimensional self-consistent fluid model. The results show that before a discharge bifurcates into a period-doubling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Since different discharge modes can influence the stability of DBDs in terms of the density and composition of active species in discharge plasmas and then impact their efficacy in related applications [12,13], the investigation on the control of nonlinear modes is valuable and imperative both in theoretical and practical aspects. It is worth noting that before bifurcating into other nonlinear modes from SP1, the discharge always first transforms into the asymmetric mode as a transition phase [14]. Therefore, investigating the mechanisms related to the asymmetric discharge mode could serve as a stepping-stone for the interpretation of other, more complex nonlinear behaviors in DBDs and deserve more attention.…”
Section: Introductionmentioning
confidence: 99%
“…Since different discharge modes can influence the stability of DBDs in terms of the density and composition of active species in discharge plasmas and then impact their efficacy in related applications [12,13], the investigation on the control of nonlinear modes is valuable and imperative both in theoretical and practical aspects. It is worth noting that before bifurcating into other nonlinear modes from SP1, the discharge always first transforms into the asymmetric mode as a transition phase [14]. Therefore, investigating the mechanisms related to the asymmetric discharge mode could serve as a stepping-stone for the interpretation of other, more complex nonlinear behaviors in DBDs and deserve more attention.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that the density of residual CO 2 + ions is very small at the beginning of the first voltage period in the P2 discharge and each voltage period in the P1 discharge. However, at the beginning of the second voltage period in P2 discharge, many CO 2 + ions produced by the first voltage period remain in the sheath region, and these CO 2 + ions make the gas easier to be ignited at a lower voltage, thereby reducing the breakdown and discharge current of subsequent discharge [22,45] . According to Figure 8a, it can be found that although the positive column in the discharge gap completely disappears, the CO 2 + ions staying in the sheath region still affect the subsequent discharge.…”
Section: Resultsmentioning
confidence: 99%
“…The normal DBD driven by a sinusoidal voltage is characterized by only one current pulse per half-cycle of the sinusoidal voltage [19,20] . However, as a complex system with strong nonlinearity, DBD could undergo temporal nonlinear behaviors under certain conditions, such as asymmetric discharge, period-doubling bifurcations, and chaos [21][22][23] . These complex nonlinear behaviors are directly related to the stability of the discharges, thus a deeper understanding of the nonlinear behaviors is beneficial to enhancing the control of the DBDs, which is very important for the decomposition of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[20]. According to our previous work about the nonlinear behaviors of the single-pulse discharge [15] , the single period discharge will first enter into a shortlived asymmetric single period discharge before the period-doubling bifurcation happens. In other words, an asymmetric single period discharge suggests that the discharge will bifurcate into a period-doubling state.…”
Section: Resultsmentioning
confidence: 99%